2017
DOI: 10.12973/eu-jer.6.1.69
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender and Attachment Styles on the Relationship between Marital Adjustment and Psychological Symptoms

Abstract: Abstract:The aim of this study is to investigate the moderating effects of attachment styles and gender on the predictive strength of marital adjustment on psychological symptoms among Turkish married individuals. Correlational model was used and the sample consisted of 178 married individuals. The data was gathered through online survey. The Turkish form of Brief Symptom Inventory (BFI) was used to measure psychological symptoms. The Turkish form of Dyadic Adjustment Scale (DAS) was used to measure marital ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In terms of building close relationships, young university students possessed attachment styles and relationship building patterns that were initiated by their attachment to their parents, but were later shaped by the effects of siblings, friends and teachers. Several studies have found that adult attachment styles of the youth were significantly correlated to happiness and subjective wellbeing (Diener & Seligman, 2002;Terzi & Cihangir Cankaya, 2009;Torquati & Raffaelli, 2004;Van Buren & Cooley, 2002;Wearden, Lamberton, Crook & Walsh, 2005;Wei, Liao, Ku & Shaffer, 2011) and psychological symptom (Koruk, 2017). In this regard, it was thought that rather than having secure attachment patterns with the parents that the attachment styles that young people build with others may affect their happiness levels.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of building close relationships, young university students possessed attachment styles and relationship building patterns that were initiated by their attachment to their parents, but were later shaped by the effects of siblings, friends and teachers. Several studies have found that adult attachment styles of the youth were significantly correlated to happiness and subjective wellbeing (Diener & Seligman, 2002;Terzi & Cihangir Cankaya, 2009;Torquati & Raffaelli, 2004;Van Buren & Cooley, 2002;Wearden, Lamberton, Crook & Walsh, 2005;Wei, Liao, Ku & Shaffer, 2011) and psychological symptom (Koruk, 2017). In this regard, it was thought that rather than having secure attachment patterns with the parents that the attachment styles that young people build with others may affect their happiness levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, threats to the attachment bond include pain, burden, or stress which may influence the attachment behavioral system. Given these challenges, older adults with illnesses are often attached to family members whom they perceive as obliged to provide care management (Koruk, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%